High-strength transparent power terminal and preparation method thereof
By adopting a composite material structure, using the ITO layer, conductive reinforcement layer and ZnO anti-corrosion coating attached to ZnO, the problems of opacity and corrosion of traditional power terminals are solved, and high-strength, transparent and good conductivity of power terminals are achieved.
Patent Information
- Application Number
- CN202510012941.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-18
AI Technical Summary
The traditional power terminal material is opaque, which makes it difficult to visually detect the connection status and is prone to corrosion, affecting service life and safety.
Power terminals are prepared using composite materials. The material is composed of ZnO-adhered ITO layer, conductive reinforcement layer and ZnO anti-corrosion coating. The conductive reinforcement layer is prepared from COC powder, carboxy PMMA, PEG and chelate. Nb:TiO2 is closely connected to the chelate to form a transparent conductive material.
It realizes high strength, transparency and good conductivity of power terminals, avoids corrosion problems of traditional metal materials, and supports visual connection status detection.
Smart Images

Figure CN119852753A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of power terminals, and in particular relates to a high-strength and transparent power terminal and a preparation method thereof. Background Art
[0002] In the current power system, power terminals are key components of power connections, used to connect cables and electrical equipment. Traditional power terminals are mostly made of metal materials such as copper or aluminum to ensure good conductivity and high cycle fatigue. However, these metal materials are opaque and cannot provide visual connection status, which brings inconvenience to detection and maintenance; in addition, metal terminals are susceptible to corrosion, affecting their service life and safety.
[0003] In the prior art, there have been experimental studies on the surface coating of power energy-saving terminal blocks. Zheng Beiji et al. provided a method for preparing power terminals (Zheng Beiji, Zhang Xiangjun, Yang Wentao, Zhang Bing, Shaanxi Electric Power, 2015, Vol. 43, No. 11), using 5 TRT-50 copper-based energy-saving terminal blocks as test samples, the surfaces of the terminal blocks were electroplated with tin, silver and copper-tin-zinc ternary alloy, respectively, the coating surfaces of the 5 terminal blocks were dense and smooth, without bubbles, sand holes, cracks, roughness and leakage and other macroscopic visible defects, and the surface was free of rust or discoloration, but the resistance value of electroplated tin was 44.76μΩ, the resistance value of electroplated silver was 36.46μΩ, and the resistance value of electroplated copper-tin-zinc ternary alloy was 39.22μΩ.
[0004] It can be seen that the above-mentioned conventional power terminals have the disadvantages of being opaque and having a high resistance value. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, an object of the present invention is to overcome the deficiencies in the prior art and provide a high-strength and transparent power terminal.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0009] The power terminal is a composite material, which includes, from bottom to top,
[0010] ZnO attached ITO layer 1;
[0011] Conductive reinforcement layer 2;
[0012] ZnO anti-corrosion coating 3;
[0013] The conductive enhancement layer is prepared from COC powder, carboxyl PMMA, PEG, chelate and Nb:TiO2, and the chelate includes one or more of DOTA, DTPA and NOTA.
[0014] As a preferred embodiment of the high-strength and transparent power terminal described in the present invention, the conductive enhancement layer comprises, by weight percentage, 10 to 20 parts of COC powder, 5 to 8 parts of carboxyl PMMA, 1 to 3 parts of PEG, 2 to 4 parts of chelate, and 5 to 10 parts of Nb:TiO2.
[0015] As a preferred solution of the high-strength and transparent power terminal described in the present invention, the particle size of the COC powder is 5 to 20 μm.
[0016] As a preferred solution of the high-strength and transparent power terminal described in the present invention, the particle size of the carboxyl PMMA is 50-100 nm.
[0017] Another object of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a high-strength and transparent power terminal.
[0018] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0019] The ZnO target is attached to the surface of the ITO film by magnetron sputtering, and the ITO film is attached on both sides to obtain an ITO layer attached with ZnO;
[0020] The COC powder and acetone are stirred evenly at room temperature, and then carboxyl PMMA is added dropwise while stirring to obtain liquid conductive particles;
[0021] The liquid conductive particles and PEG are mixed and stirred evenly, and the chelating agent is added and stirred continuously, and then the acetone is evaporated using a rotary evaporator to obtain conductive particles;
[0022] After adding Nb:TiO2 and ethanol to the conductive particles and stirring evenly, a rotary evaporator is used to evaporate the ethanol to obtain a conductive enhancer;
[0023] The conductivity enhancer is fixed to volume with ethanol and coated on the ITO layer attached with ZnO by spin coating to obtain a conductivity enhancing layer;
[0024] Liquid nano ZnO is sprayed on the conductive enhancement layer by an arc spraying method to obtain a ZnO anti-corrosion coating.
[0025] As a preferred embodiment of the method for preparing a high-strength and transparent power terminal described in the present invention, the stirring speed of the COC powder and acetone is 800-1000 rpm; the speed of dropwise adding carboxyl PMMA is 1-2 μL / s, and the temperature is 40-50°C; the speed of stirring while dropping is 1500-1800 rpm, and the time is 10-12 h.
[0026] As a preferred embodiment of the method for preparing a high-strength and transparent power terminal described in the present invention, the liquid conductive particles and PEG are mixed and stirred at a speed of 1000 rpm, a time of 2 to 3 hours, and a temperature of 45 to 50°C.
[0027] As a preferred embodiment of the method for preparing a high-strength and transparent power terminal of the present invention, the stirring time after adding the chelating agent is 5 to 6 hours.
[0028] As a preferred embodiment of the method for preparing a high-strength and transparent power terminal described in the present invention, the Nb:TiO2 and ethanol are added to the conductive particles and stirred at a speed of 1500 to 2000 rpm, for 5 to 6 hours, and at a temperature of 60 to 65°C.
[0029] As a preferred solution of the method for preparing a high-strength and transparent power terminal described in the present invention, the conductivity enhancer is fixed to 10-11 mL with ethanol.
[0030] As a preferred embodiment of the method for preparing a high-strength and transparent power terminal according to the present invention, the vacuum degree of the magnetron sputtering is 2×10 -1 Pa, target-substrate distance 10 cm, total adhesion thickness 80 nm.
[0031] As a preferred embodiment of the method for preparing a high-strength and transparent power terminal described in the present invention, the spin coating speed is 1000 rpm, the spin coating pressure is 0.4 MPa, and the spin coating thickness is 25 μm; the arc spraying pressure is 5 MPa, the spraying current is 80 A, the spraying voltage is 27 V, and the spraying distance is 100 μm.
[0032] Beneficial effects of the present invention:
[0033] (1) The COC powder in the conductive enhancer of the present invention is a transparent conductive material. Through the sequential connection of carboxyl PMMA, PEG and chelate, the transparent material Nb:TiO2 with good conductivity is finally connected to the surface of the COC powder. Among them, the COC powder with good conductivity and Nb:TiO2 can replace traditional copper or aluminum, and the transmittance is high, realizing the visual connection of the power terminal;
[0034] (2) The present invention uses DOTA, DTPA and NOTA as chelates, which have a strong connection force with the metal ion Nb, so that Nb:TiO2 with good conductivity and high transmittance is tightly coated on the outer surface of the COC powder to form a uniform cluster conductor. Multiple uniform cluster conductors increase the conductivity of the conductive enhancer, and the conductive enhancer is transparent, which meets the visual connection of the power terminal;
[0035] (3) In the present invention, carboxyl PMMA is added dropwise while stirring, so that the hydrophobic end of the carboxyl PMMA can connect with the COC powder, and the hydrophilic end of the carboxyl PMMA can be completely dissolved in acetone; the carboxyl group of the carboxyl PMMA can connect with PEG, and PEG can connect with the carboxyl group on the chelate, so that the chelate is connected to the surface of the COC powder; the Nb in Nb:TiO2 can be tightly connected with the chelate, and finally, the Nb:TiO2 that can replace copper or aluminum is evenly distributed on the surface of the COC powder and is tightly connected. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0037] Figure 1 This is a diagram of the structure of the power terminal prepared in Example 1 of the present invention;
[0038] Figure 2 This is a field emission scanning electron microscope (FE-SEM) image of the conductivity enhancer prepared in Example 1 of the present invention;
[0039] Figure 3 This is a diagram of the fatigue performance test results of the power terminal prepared in embodiment 1 of the present invention. DETAILED DESCRIPTION
[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0041] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0042] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0043] The carboxyl PMMA used in the present invention was purchased from Beijing Zhongke Keyou Nanotechnology Co., Ltd.
[0044] The COC powder used in the present invention was purchased from Dongguan Xinmiao New Materials Co., Ltd.
[0045] The Nb:TiO2 used in the present invention was purchased from Xi'an Qiyue Biotechnology Co., Ltd.
[0046] The nano ZnO used in the present invention was purchased from Beijing Beike New Materials Technology Co., Ltd.
[0047] The ZnO target material used in the present invention is purchased from Zhongke Yannuo.
[0048] The raw materials used in the present invention are commercially available unless otherwise specified.
[0049] The optical transmittance detection method of the power terminal of the present invention is: adopting ultraviolet-visible spectrophotometer (UV-vis) for characterization, using P4 type ultraviolet spectrophotometer of Shanghai Meipuda Instrument Co., Ltd.
[0050] The detection method of the block resistance of the power terminal of the present invention is: characterization is performed using a four-probe resistance tester (SZT-2A) produced by Suzhou Tongchuang Electronics Co., Ltd. and a multimeter (U1252B) produced by Agilent Technologies Co., Ltd.
[0051] The method for testing the fatigue performance of the power terminal of the present invention is: after the power terminal is bent to a deformation amount of 10%, the square resistance is measured, and then the square resistance of the power terminal with different bending times is measured.
[0052] Example 1
[0053] This embodiment provides a method for preparing a high-strength and transparent power terminal, specifically:
[0054] (1) Preparation of ITO layer with ZnO attached: The ZnO target is attached to the surface of the ITO film by magnetron sputtering. The ITO film is attached on both sides. The multi-target magnetron sputtering system uses SYSKEY from Taiwan Silicon Technology Co., Ltd. The vacuum degree of magnetron sputtering is 2×10 -1 Pa, the purity of argon is 99.999%, the target-substrate distance is 10 cm, the total thickness of the attachment is 80 nm, and the ITO layer with ZnO attachment is obtained;
[0055] (2) Preparation of a conductive reinforcement layer: 15 g of COC powder with an average particle size of 12 μm and 100 mL of acetone were mixed, stirred at 800 rpm for 20 min at room temperature, and then 6.5 g of carboxyl PMMA with an average particle size of 80 nm was added dropwise at a speed of 1 μL / s at 40°C, and stirred at a speed of 1500 rpm for 10 h to obtain liquid conductive particles;
[0056] The liquid conductive particles were mixed with 2 g PEG, stirred at 1000 rpm at 45 °C for 2 h, and then 3 g NOTA was added. After stirring for 5 h, the mixture was evenly mixed, and the acetone was evaporated using a rotary evaporator to obtain conductive particles.
[0057] 7 g of Nb:TiO2 and 100 mL of ethanol were added to the conductive particles, stirred at 60°C at a speed of 1500 rpm for 5 h, and the ethanol was evaporated using a rotary evaporator to obtain a conductive enhancer.
[0058] The conductivity enhancer was diluted to 10 mL with ethanol and coated on the ITO layer attached with ZnO by spin coating at a spin coating speed of 1000 rpm, a spin coating pressure of 0.4 MPa, and a spin coating thickness of 25 μm to obtain a conductivity enhancement layer.
[0059] (3) Preparation of ZnO anti-corrosion coating: Liquid nano ZnO was sprayed on the conductive reinforcement layer by arc spraying at a spraying pressure of 5 MPa, a spraying current of 80 A, a voltage of 27 V, and a spraying distance of 100 μm to obtain a ZnO anti-corrosion coating.
[0060] The structure of the high-strength and transparent power terminal prepared in this embodiment is as follows: Figure 1 As shown. Figure 1 It can be seen that the structure of the prepared power terminal is, from bottom to top, the first layer is the ITO layer with ZnO attached, the second layer is the conductive enhancement layer, and the third layer is the ZnO anti-corrosion coating.
[0061] The morphology of the conductive enhancer prepared in Example 1 was tested, and the results are as follows: Figure 2 As shown. Figure 2 It can be seen that the small-sized conductive particles are evenly distributed on the surface of the large-sized COC powder, and the conductive enhancer is successfully prepared on the surface.
[0062] The fatigue performance test of the power terminal prepared in Example 1 was carried out, and the results are as follows: Figure 3 As shown. Figure 3It can be seen that the resistance of the electric terminal prepared in Example 1 is slightly reduced before being bent 20 times, indicating that the lower reuse rate does not damage the conductivity of the electric terminal prepared in Example 1 of the present invention. After being bent 100 times, the resistance only increases to 16% of that before being bent, which proves that the electric terminal prepared in the present invention is high-cycle fatigue and has a high reuse rate.
[0063] Example 2
[0064] This embodiment provides a method for preparing a high-strength and transparent power terminal, and step (2) in embodiment 1 is adjusted as follows:
[0065] 20 g of COC powder with an average particle size of 20 μm and 100 mL of acetone were mixed, stirred at 800 rpm for 20 min at room temperature, and then 5 g of carboxyl PMMA with an average particle size of 50 nm was added dropwise at a speed of 1 μL / s at 40°C, and stirred at a speed of 1500 rpm for 10 h while dropping, to obtain liquid conductive particles;
[0066] The liquid conductive particles were mixed with 3 g PEG, stirred at 1000 rpm and 45°C for 2 h, and then 2 g DTPA was added. After stirring for 5 h, the mixture was evenly mixed, and the acetone was evaporated using a rotary evaporator to obtain conductive particles.
[0067] 10 g of Nb:TiO2 and 100 mL of ethanol were added to the conductive particles, stirred at 60°C at a speed of 1500 rpm for 5 h, and the ethanol was evaporated using a rotary evaporator to obtain a conductive enhancer.
[0068] The conductivity enhancer was diluted to 10 mL with ethanol and coated on the ITO layer attached with ZnO by spin coating at a spin coating speed of 1000 rpm, a spin coating pressure of 0.4 MPa, and a spin coating thickness of 25 μm to obtain a conductivity enhancement layer.
[0069] The rest of the preparation process is the same as that in Example 1 to obtain the power terminal of this embodiment.
[0070] Example 3
[0071] This embodiment provides a method for preparing a high-strength and transparent power terminal, and step (2) in embodiment 1 is adjusted as follows:
[0072] 10 g of COC powder with an average particle size of 5 μm was mixed with 100 mL of acetone, and stirred at 800 rpm for 20 min at room temperature. Then, 8 g of carboxyl PMMA with an average particle size of 100 nm was added dropwise at a speed of 1 μL / s at 40°C, and stirred at a speed of 1500 rpm for 10 h to obtain liquid conductive particles.
[0073] The liquid conductive particles were mixed with 1 g PEG, stirred at 45°C for 2 h at a speed of 1000 rpm, and then 4 g DOTA was added. After stirring for 5 h, the mixture was evenly mixed, and the acetone was evaporated using a rotary evaporator to obtain conductive particles.
[0074] 5 g of Nb:TiO2 and 100 mL of ethanol were added to the conductive particles, stirred at 1500 rpm and 60 °C for 5 h, and the ethanol was evaporated using a rotary evaporator to obtain a conductive enhancer;
[0075] The conductivity enhancer was diluted to 10 mL with ethanol and coated on the ITO layer attached with ZnO by spin coating at a spin coating speed of 1000 rpm, a spin coating pressure of 0.4 MPa, and a spin coating thickness of 25 μm to obtain a conductivity enhancement layer.
[0076] The remaining preparation process is the same as that in Example 1 to obtain the power terminal of this embodiment.
[0077] The sheet resistance and optical transmittance of the power terminals prepared in Examples 1 to 3 were tested, and the results are shown in Table 1.
[0078] Table 1 Effect of different conductive reinforcement layers on the sheet resistance and optical transmittance of power terminals
[0079]
[0080] By comparing the samples prepared in Examples 1 to 3 in Table 1, it can be seen that the square resistance of the power terminal prepared by using the raw material ratio of Example 1 is the smallest, that is, the conductivity is the best and the transmittance is the highest.
[0081] Example 4
[0082] This embodiment provides a method for preparing a high-strength and transparent power terminal, and step (2) in embodiment 1 is adjusted as follows:
[0083] 15 g of COC powder with an average particle size of 50 μm was mixed with 100 mL of acetone, and stirred at 800 rpm for 20 min at room temperature. Then, 2 g of carboxyl PMMA with an average particle size of 2 μm was added dropwise at a speed of 1 μL / s at 40°C, and stirred at a speed of 1500 rpm for 10 h while dropping, to obtain liquid conductive particles.
[0084] The liquid conductive particles were mixed with 0.5 g PEG, stirred at 45°C for 2 h at a speed of 1000 rpm, and then 1 g NOTA was added. After stirring for 5 h to mix well, the acetone was evaporated using a rotary evaporator to obtain conductive particles.
[0085] 7 g of Nb:TiO2 and 100 mL of ethanol were added to the conductive particles, stirred at 1500 rpm at 60 °C for 5 h, and the ethanol was evaporated using a rotary evaporator to obtain a conductive enhancer;
[0086] The conductivity enhancer was diluted to 10 mL with ethanol and coated on the ITO layer attached with ZnO by spin coating at a spin coating speed of 1000 rpm, a spin coating pressure of 0.4 MPa, and a spin coating thickness of 25 μm to obtain a conductivity enhancement layer.
[0087] The rest of the preparation process is the same as that in Example 1 to obtain the power terminal of this embodiment.
[0088] Example 5
[0089] This embodiment provides a method for preparing a high-strength and transparent power terminal, and step (2) in embodiment 1 is adjusted as follows:
[0090] 15 g of COC powder with an average particle size of 12 μm and 100 mL of acetone were mixed, stirred at 800 rpm for 20 min at room temperature, and then 12 g of carboxyl PMMA with an average particle size of 80 nm was added dropwise at a speed of 1 μL / s at 40°C, and stirred at a speed of 1500 rpm for 10 h while dropping, to obtain liquid conductive particles;
[0091] The liquid conductive particles were mixed with 5 g of PEG, stirred at 45°C for 2 h at a speed of 1000 rpm, and then 8 g of NOTA was added. After stirring for 5 h to mix well, the acetone was evaporated using a rotary evaporator to obtain conductive particles.
[0092] 7 g of Nb:TiO2 and 100 mL of ethanol were added to the conductive particles, stirred at 1500 rpm and 60 °C for 5 h, and the ethanol was evaporated using a rotary evaporator to obtain a conductive enhancer;
[0093] The conductivity enhancer was diluted to 10 mL with ethanol and coated on the ITO layer attached with ZnO by spin coating at a spin coating speed of 1000 rpm, a spin coating pressure of 0.4 MPa, and a spin coating thickness of 25 μm to obtain a conductivity enhancement layer.
[0094] The rest of the preparation process is the same as that in Example 1 to obtain the power terminal of this embodiment.
[0095] The sheet resistance and optical transmittance of the power terminals prepared in Examples 4 to 5 were tested, and the results are shown in Table 2.
[0096] Table 2 Effect of different conductive reinforcement layers on the sheet resistance and optical transmittance of power terminals
[0097]
[0098] Compared with Example 1, the raw material ratios of the conductive enhancers in Examples 4 and 5 are different. Comparing the data of Examples 1, 4 and 5 in Table 1, it can be seen that the power terminals prepared by raw material ratios not within the scope of the present invention will have greatly reduced effects, significantly increased sheet resistance, and reduced transmittance.
[0099] Comparative Example 1
[0100] The difference between this comparative example and Example 1 is that the carboxyl PMMA in step (2) of Example 1 is adjusted to PMMA, and the rest of the preparation process is the same as that of Example 1 to obtain the power terminal of this comparative example.
[0101] The power terminal prepared in Comparative Example 1 was subjected to sheet resistance detection and optical transmittance detection, and the results are shown in Table 3.
[0102] Table 3 Effect of carboxyl PMMA on sheet resistance and optical transmittance of power terminals
[0103]
[0104]
[0105] By comparing and analyzing the data of Example 1 and Comparative Example 1, it can be found that by replacing the PMMA containing carboxyl groups with PMMA, the square resistance of the prepared power terminal is greatly increased, indicating that the conductivity is deteriorated and the transmittance is significantly reduced. This is because the two ends of PMMA are hydrophobic and difficult to dissolve in acetone, so it is easy to agglomerate. At the same time, COC powder is also difficult to dissolve in acetone, which makes it difficult for PMMA to adhere evenly to the COC powder. Therefore, the resistance of the power terminal finally prepared is higher than that of Example 1, and the transmittance is lower than that of Example 1.
[0106] Comparative Example 2
[0107] The difference between this comparative example and Example 1 is that NOTA in step (2) of Example 1 is adjusted to EDTA, and the rest of the preparation process is the same as that of Example 1 to obtain the power terminal of this comparative example.
[0108] The power terminal prepared in Comparative Example 2 was subjected to sheet resistance detection and optical transmittance detection, and the results are shown in Table 4.
[0109] Table 4 Effect of chelates on sheet resistance and optical transmittance of power terminals
[0110]
[0111] Combining the data of Example 1 and Comparative Example 2, it can be seen that when NOTA in Example 1 is replaced by EDTA, the square resistance of the prepared power terminal will increase, indicating that replacing the chelating agent with EDTA will lead to a decrease in the conductivity of the power terminal and a decrease in the transmittance. Therefore, EDTA cannot replace NOTA.
[0112] Comparative Example 3
[0113] The difference between this comparative example and Example 1 is that Nb:TiO2 in step (2) of Example 1 is adjusted to ZnO, and the rest of the preparation process is the same as Example 1 to obtain the power terminal of this comparative example.
[0114] Comparative Example 4
[0115] The difference between this comparative example and Example 1 is that Nb:TiO2 in step (2) of Example 1 is adjusted to TiO2, and the rest of the preparation process is the same as Example 1 to obtain the power terminal of this comparative example.
[0116] The sheet resistance and optical transmittance of the power terminals prepared in Comparative Examples 3 to 4 were tested, and the results are shown in Table 5.
[0117] Table 5 Effect of Nb:TiO2 on sheet resistance and optical transmittance of power terminals
[0118]
[0119]
[0120] Combining the data of Example 1 and Comparative Examples 3-4, it can be seen that whether Nb:TiO2 is replaced by ZnO or TiO2, the sheet resistance of the power terminal will increase, that is, the conductivity will decrease, and the transmittance will also decrease. This is because ZnO or TiO2 cannot produce a good chelation with NOTA and cannot be evenly attached to the outer surface of the COC powder.
[0121] Comparative Example 5
[0122] The difference between this comparative example and Example 1 is that carboxyl PMMA is not added in step (2), and the rest of the preparation process is the same as that of Example 1 to obtain the power terminal of this comparative example.
[0123] Comparative Example 6
[0124] The difference between this comparative example and Example 1 is that PEG is not added in step (2), and the rest of the preparation process is the same as that in Example 1 to obtain the power terminal of this comparative example.
[0125] Comparative Example 7
[0126] The difference between this comparative example and Example 1 is that NOTA is not added in step (2), and the rest of the preparation process is the same as that in Example 1 to obtain the power terminal of this comparative example.
[0127] The power terminals prepared in Comparative Examples 5 to 7 were subjected to sheet resistance testing and optical transmittance testing, and the results are shown in Table 6.
[0128] Table 6 Effects of PMMA, PEG and chelate on sheet resistance and optical transmittance of power terminals
[0129]
[0130] Comparative Examples 5 to 7 do not add carboxyl PMMA, PEG and chelate respectively, while Example 1 adds all three at the same time. By comparing the data of Example 1 and Comparative Examples 5 to 7, it is found that the sheet resistance of the power terminals prepared in Comparative Examples 5 to 7 is higher than that in Example 1. This is because only when COC powder, carboxyl PMMA, PEG and chelate are connected in sequence can they be connected to Nb:TiO2, indicating that carboxyl PMMA, PEG and chelate are indispensable.
[0131] Comparative Example 8
[0132] The difference between this comparative example and Example 1 is that Nb:TiO2 is not added in step (2), and the rest of the preparation process is the same as that in Example 1 to obtain the power terminal of this comparative example.
[0133] The power terminal prepared in Comparative Example 8 was subjected to sheet resistance test and optical transmittance test, and the results are shown in Table 7.
[0134] Table 7 Effect of Nb:TiO2 on sheet resistance and transmittance of power terminals
[0135]
[0136] By comparing Example 1 and Comparative Example 8, it can be seen that if Nb:TiO2 is not added, Nb:TiO2 will not be able to replace copper or aluminum, so that the resistance of the prepared power terminal increases, that is, the conductivity decreases, and the transmittance also decreases.
[0137] Comparative Example 9
[0138] The difference between this comparative example and Example 1 is that step (1) in Example 1 is not performed, that is, ZnO is not attached to the surface of the ITO film, and the rest of the preparation method is the same as that in Example 1 to obtain the power terminal of this comparative example.
[0139] The power terminal prepared in Comparative Example 9 was subjected to sheet resistance detection and optical transmittance detection, and the results are shown in Table 8.
[0140] Table 8 Effect of preparation method on sheet resistance and transmittance of power terminals
[0141]
[0142] By comparing Example 1 and Comparative Example 9, it can be concluded that if ZnO is not attached to the ITO film during the preparation process, the sheet resistance of the power terminal will be greatly increased, indicating that the conductivity is greatly reduced and the transmittance is also reduced, which shows that it is crucial to attach ZnO to the ITO film in the preparation method.
[0143] In summary, the present invention connects the transparent conductive material COC powder, carboxyl PMMA, PEG and chelate in sequence, and the Nb in Nb:TiO2 can be tightly connected with the chelate, so that the transparent material Nb:TiO2 with good conductivity can be connected to the surface of COC powder. Among them, COC powder with good conductivity and Nb:TiO2 can replace traditional copper or aluminum, and the transmittance is high, realizing the visual connection of power terminals.
[0144] The present invention adopts DOTA, DTPA and NOTA as chelates, which can have a strong connecting force with the metal ion Nb, so that Nb:TiO2 with good conductivity and high transmittance is tightly coated on the outer surface of COC powder to form a uniform cluster conductor. Multiple uniform cluster conductors increase the conductivity of the conductive enhancer, and the conductive enhancer is transparent, which meets the visual connection of the power terminal.
[0145] Finally, the power terminal prepared by the present invention has the advantages of low resistance, good conductivity, high transmittance, strong fatigue resistance, and high reusability, thereby realizing the visual connection of the power terminal.
[0146] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A high-strength and transparent power terminal, characterized in that: The power terminal is a composite material, which includes, from bottom to top, ITO layer with ZnO attached; Conductive reinforcement layer; ZnO anti-corrosion coating; The conductive enhancement layer is prepared from COC powder, carboxyl PMMA, PEG, chelate and Nb:TiO2, and the chelate includes one or more of DOTA, DTPA and NOTA.
2. The high-strength and transparent power terminal according to claim 1, characterized in that: The conductive reinforcement layer comprises, by weight of raw materials, 10 to 20 parts of COC powder, 5 to 8 parts of carboxyl PMMA, 1 to 3 parts of PEG, 2 to 4 parts of chelate, and 5 to 10 parts of Nb:TiO2.
3. The high-strength and transparent power terminal according to claim 2, characterized in that: The particle size of the COC powder is 5 to 20 μm.
4. The high-strength and transparent power terminal according to claim 2, characterized in that: The particle size of the carboxyl PMMA is 50-100 nm.
5. The method for preparing a high-strength and transparent electronic terminal according to claim 1, characterized in that: include, The ZnO target is attached to the surface of the ITO film by magnetron sputtering, and the ITO film is attached on both sides to obtain an ITO layer attached with ZnO; The COC powder and acetone are stirred evenly at room temperature, and then carboxyl PMMA is added dropwise while stirring to obtain liquid conductive particles; The liquid conductive particles and PEG are mixed and stirred evenly, and the chelating agent is added and stirred continuously, and then the acetone is evaporated using a rotary evaporator to obtain conductive particles; After adding Nb:TiO2 and ethanol to the conductive particles and stirring evenly, a rotary evaporator is used to evaporate the ethanol to obtain a conductive enhancer; The conductivity enhancer is fixed to volume with ethanol and coated on the ITO layer attached with ZnO by spin coating to obtain a conductivity enhancing layer; Liquid nano ZnO is sprayed on the conductive enhancement layer by an arc spraying method to obtain a ZnO anti-corrosion coating.
6. The method for preparing a high-strength and transparent electronic terminal according to claim 5, characterized in that: The stirring speed of the COC powder and acetone is 800-1000 rpm; the speed of dropwise adding carboxyl PMMA is 1-2 μL / s, and the temperature is 40-50° C.; the speed of stirring while dropping is 1500-1800 rpm, and the time is 10-12 hours.
7. The method for preparing a high-strength and transparent electronic terminal according to claim 5, characterized in that: The liquid conductive particles and PEG are mixed and stirred at a speed of 1000 rpm, a time of 2 to 3 hours, and a temperature of 45 to 50°C.
8. The method for preparing a high-strength and transparent electronic terminal according to claim 5, characterized in that: The stirring time after adding the chelating agent is 5 to 6 hours.
9. The method for preparing a high-strength and transparent electronic terminal according to claim 5, characterized in that: The Nb:TiO2 and ethanol are added to the conductive particles and stirred at a speed of 1500-2000 rpm for 5-6 hours at a temperature of 60-65°C.
10. The method for preparing a high-strength and transparent electronic terminal according to claim 5, characterized in that: The conductivity enhancer is diluted to 10-11 mL with ethanol.